Assessment of exposure to wheat flour and the shape of its relationship with specific sensitization - Peretz, C; de Pater, N; de Monchy, J; Oostenbrink, J; Heederik, Dick (Scandinavian Journal of Work, Environment & Health, 2005)
' ' OBJECTIVES ': 'Dust and wheat-allergen exposure were assessed among bakers, flour millers, and bakery-ingredient producers, and the risk for sensitization was studied. ' ' METHODS ': 'About 520 inhalable dust and wheat-allergen measurements were made among 270 Dutch workers. Data on sensitization to wheat and common allergens (atopy) were also available. Exposure was estimated according to the sector of industry, job title, and tasks. The shape of the relationship between sensitization and exposure was studied using a two-stage modeling approach: semi-parametric generalized additive modeling and, consequently, a simple description of the relationship using a parametric logistic model. To reduce the effect of exposure measurement errors (attenuation), a combination of the actual measured exposure and variance-weighted estimates of exposure was used. ' ' RESULTS ': 'The effect of exposure to both inhalable dust and wheat allergens on sensitization was described best by a linear relationship in three industries and a quadratic relationship in one industry. The relation for the whole study population was best described as quadratic, and the probability of sensitization increased with exposure up to ~2.7 mg/m3 for inhalable dust and ~25.7 µg EQ/m3 for wheat allergens. The risk decreased at higher exposures (P=0.0121 and P=0.0731 for dust and wheat, respectively). Atopy and sector of industry modified the sensitization risk significantly in all the analyses. Using a variant-weighted estimator to calculate exposures corrected for the bias and resulted in almost the same point risk estimators. ' ' CONCLUSIONS ': 'Exposure–response relationships for allergens may be nonlinear and differ between industries. A threshold is not indicated on which to base occupational exposure standards; alternatively, other approaches, such as benchmarking, seem warranted.
Keywords: atopy; baker; exposure; exposure-response; model; occupational exposure; sensitization; variance component; wheat flour